Factors associated with attendance to early childhood education programs in Malaysia: results from the national health and morbidity survey (Maternal and child health) 2016 - Sooryanarayana, Rajini; Ganapathy, Shubash Shander; Abdul Manaf, Rosliza; Mohammad, Nik Mazlina; Ibrahim Wong, Norazizah; Ahmad, Noor Ani; Chan, Ying Ying; Sahril, Norhafizah; Abd Wahab, Nor'Ain; Nik Shahein, Nik Adilah; Aris, Tahir (Malaysian Public Health Physicians’ Association, 2021)
The National Health and Morbidity Survey (NHMS) 2016 was a nationwide cross-sectional survey focusing on maternal and child health. This study aimed to identify the prevalence of, and factors associated with early childhood educational program (ECE) attendance among children aged three to five years in Malaysia. Attendance to ECE has been shown to enhance children’s development, yet there is no national information on ECE attendance in Malaysia, where attendance is not compulsory for children below five years. Parents were interviewed face-to-face utilising a validated questionnaire from the UNICEF Multiple Indicator Cluster Survey using mobile devices. Multivariate logistic regression analysis was performed to identify factors associated with ECE attendance. Half (53.4%) of children aged three to five years in Malaysia attend ECE. Older children aged four to five were six times more likely to attend ECE than children three to four years. Malaysian children of Chinese ethnicity were thrice as likely than ethnic Malays to attend ECE. Children with access to >3 children’s books were twice more likely to attend ECE than those who had access to <3 books. Unemployed mothers were less likely to send their children to ECE than mothers employed in civil service. More awareness on the importance and benefits of ECE attendance on children’s development is necessary so that younger children benefit from ECE.